Voltage error phase locked loop (PLL) based model adaptive sensorless vector control algorithm for induction motors - Ozdemir, Sadik; Sozer, Yilmaz; Umurkan, Nurettin (Conference proceedings - IEEE Applied Power Electronics Conference and Exposition, 2017)
This study presents a speed sensorless indirect field oriented control (IFOC) method for induction motors (IMs). The proposed method is a novel Model Adaptive Controller (MAC) method and needs only steady-state q-axis stator voltage equation to estimate the rotor position. The proposed MAC system does not need a reference loop since the estimated voltage is directly compared with measured one. The state equations needed for estimation do not require any rotor parameters which makes the system immune to the variation of rotor parameters. Moreover, this unique calculation eliminates the requirement of flux estimation thus; the method is less sensitive to pure integration problems. The method is verified with simulation and experiments and proven to be accurate at wide operating speed ranges.